(untitled) (EU and comparative law issues and challenges series (ECLIC), 2019)
Rights in the digital world affect our property in a special way. This paper aims to explain how users right in a digital world reflect on user’s estate of inheritance. Firstly, it is explained what digital content is and what digital services are. After that, digital content and services are discussed from the user’s point of view having in mind rights that users have in a digital world. Although those rights contain a right to use data or services they are created and regulated through different provisions (copyright, intellectual property, ownership or licences). Under the principle of universal succession, everything that belonged to decedent can belong to his or her heirs unless it is explicitly regulated otherwise or rights are strictly personal. Despite this principle there are some rights in the digital world that cannot belong to the heirs. Also, existence of a digital inheritance might cause some practical problems.